Learning Bayesian models with R : become an expert in Bayesian machine learning methods using R and apply them to solve real-world big data problems /: become an expert in Bayesian machine learning methods using R and apply them to solve real-world big data problems. (2015) - Koduvely, Hari M
No abstract available